1988
DOI: 10.1159/000242868
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Serum Glucose and Galactose Concentrations in Term Newborn Infants after Milk Feeding

Abstract: Galactose and glucose concentrations were measured in peripheral blood in relation to ad libitum milk feeding in 11 healthy near-term infants. Galactose and glucose concentrations before feeding averaged 1.06 ± 0.21 and 60.3 ± 3.2 mg/dl, respectively. After feedings containing 0.76–2.68 g lactose/kg body weight, both galactose and glucose rose by approximately 35%. Galactose concentrations rose by 0.72 ± 0.10 mg/dl at 30 min after feeding, while glucose concentration rose by 23.3 ± 2.5 mg/dl at 30 min after fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 11 publications
3
19
1
Order By: Relevance
“…And in eighteen 18-28-dayold normal neonates, levels were 0.05 8 0.039 mmol/l (0.96 8 0.71 mg/dl), with galactose determined by enzymatic methods [5] . Galactose levels in our 48-hour-old newborns are similar to those of Mizoguchi et al [5] and lower than those found by Siegel et al [4] ; however, differences in protocols must be considered, such as infant age, the time after milk ingestion when samples were collected, and type of milk. Galactose and glucose concentrations are higher in preterm or full-term formulas than breast milk [27] .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…And in eighteen 18-28-dayold normal neonates, levels were 0.05 8 0.039 mmol/l (0.96 8 0.71 mg/dl), with galactose determined by enzymatic methods [5] . Galactose levels in our 48-hour-old newborns are similar to those of Mizoguchi et al [5] and lower than those found by Siegel et al [4] ; however, differences in protocols must be considered, such as infant age, the time after milk ingestion when samples were collected, and type of milk. Galactose and glucose concentrations are higher in preterm or full-term formulas than breast milk [27] .…”
Section: Discussionsupporting
confidence: 85%
“…The absence of an association between galactose and glucose blood levels in the cord and 48-hour-old infant suggests that the newborn has established its own metabolism independently from the fetal metabolism and that blood galactose is very dependent on milk ingestion. Although it was not possible to demonstrate a direct association between ingested galactose, through maternal milk lactose, and blood galactose levels in newborns, there is indirect evidence in literature connecting milk ingestion and blood galactose levels [4,7] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[12][13][14][15] The aim of this study was to determine whether delayed recognition memory for spoken words is better after a typical feeding than before and whether blood glucose levels are associated with memory. Healthy 2-to 3-day-old infants were studied under naturalistic conditions; that is, memory was compared before and after a routine breast or formula feeding.…”
Section: Methodsmentioning
confidence: 99%
“…Newborn blood glucose levels after a feeding tend to be highest at 30 to 90 minutes and decline steadily to baseline values after 90 to 120 minutes. [12][13][14][15] Because previous studies suggested that only some infants have postprandial blood glucose levels that increase up to levels that are found after a memory enhancing dose of glucose (2 g/kg), twice as many infants were tested after a feeding as before (two thirds versus one third). Blood glucose was measured in all infants after the memory test (mean Ϯ SD: 16.4 Ϯ 8.8 minutes).…”
mentioning
confidence: 99%